Struktur Waktu Religius dalam Kebudayaan Melayu Sungai Rokan - Junaidi Syam (Jurnal Sosiologi Agama, 2014)
The concept of “time” should be really crucial and strategic in social science, culture and the humanities, because ‘time’ can influence and change ideas and human actions, so cultural systems experience dynamics as time goes. Inevitably, not aware or cognizant, the potency and existence of the concept of time to engage naturally presents in mondial life, supporting profane and religious activities for religious theocentrists, anthropocentric belief, and for the atheist either. There are three classifications of the concept of time. The first concept of time that is believed is nothingness and shore less at the end; it is called also as single time. The second concept of time is linear, that is the time of being continuous walk and cannot be reversed, the back or backward. The third concept of time is of a cycled time that continues over and over as if appear lost, arising drowning, born and then death and get reborn, stand up and collapse so endlessly. I try to make a connotative interpretative model of visual of praying motion seen in a structural model of cyclical time. I hope the effort of associative exegesis become the manner or an instance of explaining how to work the transformation of the nature of the unconscious mind with the delineation of being logical, to understand the dynamics and dialectics of religious activity of traditional society.